Description of a New Species of Eusynstyela (Ascidiacea: Stolidobranchia) from Okinawa, Japan with Molecular Insight into Its Phylogenetic Position - Naohiro Hasegawa (Species Diversity)
The colonial styelid genus Eusynstyela Michaelsen, 1904 comprises 12 species. Seven colonies of Eusynstyela were collected via SCUBA diving from three coastal sites in Okinawa, Japan, between 2018 and 2023. Morphological observations in this study identified these specimens as a new species, described here as Eusynstyela sesokoensis sp. nov. This species can be distinguished from its congeners by the following characteristics: i) ten oral tentacles, ii) twelve stomach plications, iii) absence of a stomach caecum, iv) no lobes on the anal rim, and v) two testes per gonad. Intraspecific variations were observed in zooid coloration and the number of longitudinal vessels on the pharyngeal folds. The molecular phylogenetic analysis based on a partial sequence of 18S rRNA and the mitochondrial cytochrome c oxidase subunit I genes indicates a possible sister relationship between the new species and E. latericius (Sluiter, 1904).